2012
DOI: 10.1128/aac.06169-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of BMS-790052 on Hepatitis C Virus Genotype 4 NS5A

Abstract: The antiviral profile of BMS-790052, a potent hepatitis C virus (HCV) replication complex inhibitor targeting nonstructural protein NS5A, is well characterized for HCV genotype-1. Here, we report that BMS-790052 inhibits hybrid replicons containing HCV genotype-4 NS5A genes with 50% effective concentrations (EC 50 s) ranging from 7 to 13 pM. NS5A residue 30 was an important site for BMS-790052-selected resistance in the hybrid replicons. Our results support the potential of BMS-790052 as a valuable component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Resistance-associated amino acid substitutions in NS5A were observed at positions similar to those reported for other genotypes within the first 100 amino acids (aa) of NS5A. The availability of GT-5a and GT-6a NS5A hybrid replicons, together with authentic or hybrid replicons from genotypes 1 to 4 (2,(14)(15)(16), enabled direct comparison of the resistance barriers of DCV in these diverse genotypes by using replicon elimination assays (13). These studies revealed that GT-1b has the highest barrier of resistance to DCV, while GT-2a has the lowest resistance barrier, with a relative rank order of 1b Ͼ 4a Ն 5a Ͼ 6a Х 1a Ͼ 2a JFH Ͼ 3a Ͼ 2a M31.…”
Section: Aclatasvir (Dcv [Bms-790052]) Is a Cross-genotypic Ns5amentioning
confidence: 68%
See 1 more Smart Citation
“…Resistance-associated amino acid substitutions in NS5A were observed at positions similar to those reported for other genotypes within the first 100 amino acids (aa) of NS5A. The availability of GT-5a and GT-6a NS5A hybrid replicons, together with authentic or hybrid replicons from genotypes 1 to 4 (2,(14)(15)(16), enabled direct comparison of the resistance barriers of DCV in these diverse genotypes by using replicon elimination assays (13). These studies revealed that GT-1b has the highest barrier of resistance to DCV, while GT-2a has the lowest resistance barrier, with a relative rank order of 1b Ͼ 4a Ն 5a Ͼ 6a Х 1a Ͼ 2a JFH Ͼ 3a Ͼ 2a M31.…”
Section: Aclatasvir (Dcv [Bms-790052]) Is a Cross-genotypic Ns5amentioning
confidence: 68%
“…Prior studies using the in vitro replicon system indicated that DCV should be an effective antiviral agent against HCV genotypes 1 to 4 (2,(13)(14)(15)(16). Here, we report the antiviral activity and resistance profiles of DCV against hybrid replicons with NS5A sequences derived from GT-5a and GT-6a clinical isolates.…”
Section: Aclatasvir (Dcv [Bms-790052]) Is a Cross-genotypic Ns5amentioning
confidence: 99%
“…BMS-791325 was synthesized at Bristol-Myers Squibb. Daclatasvir (DCV; NS5A replication complex inhibitor) and asunaprevir (ASV; NS3 protease inhibitor) were previously described (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Cell Lines and Hcv Inhibitorsmentioning
confidence: 99%
“…However, the increased incidence of adverse events associated with interferon-based regimens triggered the development of interferon-free therapeutic combinations . In vitro studies show that daclatasvir, an NS5A inhibitor, has a pan-genotypic activity with picomolar potency and pharmacokinetic characteristics allowing for single daily dosage regimens Wang et al, 2012). It acts via inhibiting the NS3 protease enzyme and therefore, preventing NS5A hyperphosphorylation, leading to inhibition of viral replication complex formation (Lee et al, 2011;Qiu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hezode et al (2014) reported that patients with CC IL28B genotype had a higher chance of achieving SVR, compared to those with a non-CC genotype, regardless of therapy . Also, as shown by in vivo and in vitro studies, the combination of L30 polymorphism and IL28B non-CC genotype can significantly increase daclatasvir resistance (Wang et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%